2023
DOI: 10.1096/fj.202201469r
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine exerts anti‐atherosclerotic and ‑plaque‐stabilizing effects targeting foam cell formation

Abstract: Colchicine is a broad-acting anti-inflammatory agent that has attracted interest for repurposing in atherosclerotic cardiovascular disease. Here, we studied its ability at a human equivalent dose of 0.5 mg/day to modify plaque formation and composition in murine atherosclerosis and investigated its actions on macrophage responses to atherogenic stimuli in vitro. In atherosclerosis induced by high-cholesterol diet, Apoe −/− mice treated with colchicine had 50% reduction in aortic oil Red O + plaque area compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…However, the oil red O staining demonstrated no significant change in lipid contents within plaque after treatment of colchicine or col@PBNP@HA. Previous studies have suggested that inflammation and foam cell formation share many similar pathways and that colchicine can inhibit foam cell formation. , Nevertheless, the results of the present research indicated that col@PBNP@HA had no effect on foam cell formation, which may be attributed to the discrepancy in the administration period.…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…However, the oil red O staining demonstrated no significant change in lipid contents within plaque after treatment of colchicine or col@PBNP@HA. Previous studies have suggested that inflammation and foam cell formation share many similar pathways and that colchicine can inhibit foam cell formation. , Nevertheless, the results of the present research indicated that col@PBNP@HA had no effect on foam cell formation, which may be attributed to the discrepancy in the administration period.…”
Section: Resultscontrasting
confidence: 83%
“…It is necessary to verify the good in vivo biocompatibility and low organ toxicity of col@PBNP@HA. In this study, we applied the nanoparticles at a colchicine dose of 0.1 mg/kg according to previous reports . Histomorphological analysis of the tissue of hearts, livers, spleens, lungs, and kidneys 7 d after single injection showed no organ impairment, including necrosis, hemorrhage, and inflammatory cell infiltration (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colchicine, an important anti-inflammatory molecule that has been effective in the prevention of major adverse cardiovascular events, has been suggested as an NLRP3 inflammasome inhibitor. Preclinically, the administration of colchicine in murine and human macrophages treated with oxidized LDL resulted in the inhibition of NLRP3 inflammasome formation [ 57 ]. Moving to clinical studies, Robertson et al had initially proven that the administration of colchicine in patients with ACS resulted in lower expression of NLRP3 inflammasome markers (IL-1β, IL-18, pro-caspase-1, and caspase-1) from peripheral venous blood monocytes [ 58 ].…”
Section: Inflammasome Modulation: Therapeutic Perspectivesmentioning
confidence: 99%
“…Studies showed that colchicine treatment could reduce the risk of cardiovascular events including myocardial infarction, chronic coronary disease, recurrent pericarditis and atrial fibrillation [ 10 , 12 , 15–17 ]. Recently, it was found that colchicine exerted anti-atherosclerotic and plaque-stabilizing effects by inhibition of foam cell formation and inflammation in murine atherosclerosis [ 18 ], and more recently (in June 2023), low-dose colchicine (0.5 mg/d orally) was approved to reduce the risk of cardiovascular events in adult patients with established atherosclerotic disease or with multiple risk factors for cardiovascular disease by the U.S. Food and Drug Administration [ 19 ].…”
Section: Introductionmentioning
confidence: 99%